Development of Professional Competence of Future Psychologists in Providing Psychological Assistance to Children and Adolescents with Psychological Trauma: An Integrative Approach Informed by Human Psychology and Zoological Perspectives - Victoriia Overchuk; Nataliia Schell; Oksana Solovei-Lagoda; Natalia Lapshova; Serhii Mishchuk; Zoryna Boiarska (The Bioscan, 2025)
This study explores the development of professional competence among future psychologists providing psychological assistance to children and adolescents experiencing psychological trauma. It examines the essential knowledge, skills, and attitudes required for effective trauma-informed care. Utilizing a qualitative approach involving semi-structured interviews and focus groups with psychology students (n=40) and practicing psychologists (n=40), the research identifies key competencies and challenges. The findings highlight the necessity of specialized knowledge (including trauma-informed practices and evidence-based interventions), practical skills (like rapport-building and culturally sensitive communication), and personal attributes (such as empathy and self-reflection). Integrating insights from human psychology with broader biological perspectives on stress and development, partly informed by comparative research documented in comprehensive databases like Zoological Record, can enrich psychologist training. The results contribute to enhancing training programs to better prepare future psychologists for addressing the complex biopsychosocial needs of traumatized youth.